Statistical analysis plan for the control of blood pressure and risk attenuation-rural Bangladesh, Pakistan, Sri Lanka (COBRA-BPS) trial: A cluster randomized trial for a multicomponent intervention versus usual care in hypertensive patients - Gandhi, M (2020)
10.1186/s13063-018-3022-8